The Giving Tree. - Silverstein, Shel. (New York, Harper & Row, 1964)
A young boy grows to manhood and old age experiencing the love and generosity of a tree which gives to him without thought of return.
Elementary School Library Collection (Bro-Dart)
Basal Reading Program
2.9
K-3
Keywords: Trees -- Fiction; Trees -- Fiction